Isothermal hydrogen absorption process of Pd-capped Mg films traced by ion beam techniques and optical methods - Abejon D.; Prieto P.; Kim J.K.; Redondo-Cubero A.; Crespillo M.L.; Leardini F.; Ferrer I.J.; Garcia G.; Ares J.R. (National Engineering Research Center for Magnesium Alloys of China, Chongqing University, 2024)
Pd-capped nanocrystalline Mg films were prepared by electron beam evaporation and hydrogenated under isothermal conditions to investigate the hydrogen absorption process via ion beam techniques and in situ optical methods. Films were characterized by different techniques such as X-ray diffraction (XRD) and scanning electron microscopy (SEM). Rutherford backscattering spectrometry (RBS) and elastic recoil detection analysis (ERDA) provided a detailed compositional depth profile of the films during hydrogenation. Gas-solid reaction kinetics theory applied to ERDA data revealed a H absorption mechanism controlled by H diffusion. This rate-limiting step was also confirmed by XRD measurements. The diffusion coefficient (D) was also determined via RBS and ERDA, with a value of (1.1±0.1)·10